Ali Shari’ati’s revolutionary Islamic thought and its relevance to the contemporary socio-political transformation - Anjar Nugroho; Tulus Warsito Surwandano (Indonesian Journal of Islam and Muslim Societies, 2017)
Ali Shari’ati emerged as an enlightened intellectual figure in the phenomenonof the authoritarian and oppressive power of the Syah Pahlavi regime. Shari’atiappeared as a pioneer of radical ideas about Islam and the revolution whichstemmed from the Shi’a teachings that had been grafted into the revolutionary tradition of the Third World and Marxism. Shari’ati succeeded in establishing a revolutionary Islamic ideology that became the basis of the mass collective consciousness against the regime of the Syah. In Shari’ati’s thought, Islam is an emancipatory ideology and liberation. The progressive and revolutionary view of Shari’ati’s Islam derives from a belief system of tauhid. While tauhid in Shari’ati’s view is the unity among God, man and the universe, the society which is full of social discrimination, injustice, and arbitrariness can be categorized as Shirk, the opponent of tauhid. In the context of the Iranian revolution, the Shari’ati’s Islamic thought and ideology became the fourth  t-text-stroke-width: 0px; " bridge or road from the ideological stalemate of the pre-revolutionary opposition movement, which is between secularist-nationalist, Marxist-Communistand Islamic Fundamentalism. Further, Shari’ati’s ideology paved the way forthe acceptance of Imam Khomeini as a revolutionary leader. This paper aimsto contextualize Ali Shari’ti’s views on socio-political change in Indonesia.Ali Shari’ati muncul menjadi sosok intelektual tercerahkan dalam fenomenakekuasaan rezim Syah Pahlevi yang otoriter dan menindas. Shari’ati lalu tampilsebagai pelopor gagasan-gagasan radikal tentang Islam dan revolusi yang bersumberdari ajaran Syi’ah yang sudah dicangkokkan dengan tradisi revolusioner DuniaKetiga dan Marxisme. Ali Shari’ati berhasil membangun ideologi Islam revolusioneryang kemudian menjadi basis kesadaran kolektif massa menentang kekuasaan rezimSyah. Dalam pemikiran Shari’ati, Islam adalah sebuah ideologi emansipasi danpembebasan. Pandangan Islam Ali Shari’ati yang progresif dan revolusionerbersumber pada satu sistem keyakinan yaitu tauhid. Jika tauhid dalam pandanganShari’ati adalah kesatuan antara Tuhan, manusia dan alam semesta, maka kondisimasyarakat yang penuh diskriminasi sosial, ketidakadilan, dan kesewenang-wenangandapat dikategorikan sebagai syirk, lawan dari tauhid. Dalam konteks revolusi Iran,tawaran pemikiran dan ideologi Islam Syari’ati menjadi jembatan atau jalan keempatdari kebuntuan ideologi gerakan oposisi pra-revolusi, yaitu antara nasionalis-sekuler,Marxis-Komunis dan Fundamentalisme Islam. Ideologi Shari’ati melapangkanjalan bagi diterimanya Imam Khomeini sebagai pemimpin revolusioner. Tulisanini hendak mengkontekstualisasikan pemikiran Ali Shari’ati dalam perubahan sosialpolitik di Indonesia.